2023
DOI: 10.1002/adfm.202301228
|View full text |Cite
|
Sign up to set email alerts
|

Switching Monomer‐to‐Excimer Fluorescence by Noncovalent Interaction Competition Strategy

Abstract: Noncovalent fluorescence switching materials with specific molecular packing motifs for desired performance are difficult to design accurately due to the complexity of intermolecular interactions. Herein, a noncovalent interaction competition strategy to design fluorescence-switching materials by fine-modulating hydrogen-bond and π-π interactions is proposed. Hydrogen bonds are generated by nitrogen/oxygen-containing units while π-π interactions are generated between polycyclic aromatic hydrocarbons. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Among the common anti-counterfeiting technologies, advanced stimuli-fluorochromic materials provide a much higher level of security, which is because the encrypted information can only be identified when external stimuli is applied. 16,98,105 Here, a representative example of anti-counterfeiting based on stimuli-fluorochromic smart materials will be detailed. 16 A fluorescence-switchable material based on fine-modulating π–π interaction and hydrogen bonds exhibits promising application in time-dependent anti-counterfeiting, 16 which is attributed to the reversible assembly conversion with high-contrast monomer-to-excimer fluorescence-switching induced by the laser-produced thermal stimulus.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the common anti-counterfeiting technologies, advanced stimuli-fluorochromic materials provide a much higher level of security, which is because the encrypted information can only be identified when external stimuli is applied. 16,98,105 Here, a representative example of anti-counterfeiting based on stimuli-fluorochromic smart materials will be detailed. 16 A fluorescence-switchable material based on fine-modulating π–π interaction and hydrogen bonds exhibits promising application in time-dependent anti-counterfeiting, 16 which is attributed to the reversible assembly conversion with high-contrast monomer-to-excimer fluorescence-switching induced by the laser-produced thermal stimulus.…”
Section: Applicationsmentioning
confidence: 99%
“…1–12 Among them, stimuli-fluorochromic smart materials (SFSMs), whose photoluminescence properties can be switched by applying different external stimuli, have attracted tremendous attention due to their highly sensitive response and easy visualization. 13–31 As an example of advanced functional materials, stimuli-fluorochromic smart materials exhibit great application potential for applications such as sensors, 22,26,32–43 information storage, 44–47 bioimaging, 48–50 information encryption and smart displays, 27,31,51–76 green printing, 13,55,77–89 smart optoelectronic devices, 90–93 and anti-counterfeiting. 20,24,94–110 During the past few decades, there have been numerous reports on the design and synthesis of various emission color-switching SFSMs in both solution and the solid state, including conformation-dependent organic π-conjugated molecules (π-conjugated and non-conjugated), 81,111–117 organometallic compounds, 118 and host–guest complexes.…”
Section: Introductionmentioning
confidence: 99%
“…26 In the crystal form, two pyrene molecules in a dimeric stacking structure show face-to-face π–π stacking; 23 however, chemical modification of the pyrene at the molecular level always results in the loss of the pyrene dimer stacking due to multiple factors, such as electrostatic potential (ESP), steric hindrance, and intermolecular interaction. 27–33 Research specializing in the pyrene-based dimer stacking is actually reported less. 32–38 Some approaches to the construction of the pyrene-based dimer stacking have been demonstrated to be effective, including molecular crystal engineering, 31–34 cocrystal engineering, 39 intramolecular chemical modification, 40,41 and supramolecular assembly in cavity host.…”
Section: Introductionmentioning
confidence: 99%
“…27–33 Research specializing in the pyrene-based dimer stacking is actually reported less. 32–38 Some approaches to the construction of the pyrene-based dimer stacking have been demonstrated to be effective, including molecular crystal engineering, 31–34 cocrystal engineering, 39 intramolecular chemical modification, 40,41 and supramolecular assembly in cavity host. 42 Thereinto, the molecular packing structures achieved using molecular crystal engineering are suitable for practical applications; however, they are unpredictable, and their construction is more challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation